2018
DOI: 10.3389/fnins.2018.00485
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Habenula Gone Awry in Depression: Bridging Cellular Adaptations With Therapeutics

Abstract: Depression is a highly heterogeneous disease characterized by symptoms spanning from anhedonia and behavioral despair to social withdrawal and learning deficit. Such diversity of behavioral phenotypes suggests that discrete neural circuits may underlie precise aspects of the disease, rendering its treatment an unmet challenge for modern neuroscience. Evidence from humans and animal models indicate that the lateral habenula (LHb), an epithalamic center devoted to processing aversive stimuli, is aberrantly affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 53 publications
4
19
0
1
Order By: Relevance
“…In concordance with these human data, we find that acute stress through introduction of intermittent shock trials reduces licking for a sucrose reward, consistent with anhedonic behavior (42)(43)(44)(45)(46)(47). Previous studies in rodents found that stress increases metabolic and neuronal activity in the LHb (17,(26)(27)(28)(29), indicating that stress causes depression-relevant behaviors by increasing baseline tonic or bursting LHb activity in vivo (1,13,18,29,56). Our results suggest an unexpected, additional mechanism for how stress decreases reward-motivated behavior: negatively distorted RPE signaling in LHb neurons.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In concordance with these human data, we find that acute stress through introduction of intermittent shock trials reduces licking for a sucrose reward, consistent with anhedonic behavior (42)(43)(44)(45)(46)(47). Previous studies in rodents found that stress increases metabolic and neuronal activity in the LHb (17,(26)(27)(28)(29), indicating that stress causes depression-relevant behaviors by increasing baseline tonic or bursting LHb activity in vivo (1,13,18,29,56). Our results suggest an unexpected, additional mechanism for how stress decreases reward-motivated behavior: negatively distorted RPE signaling in LHb neurons.…”
Section: Discussionsupporting
confidence: 89%
“…In particular, the LHb provides reward prediction error (RPE) (2) signals-the difference between expected and actual reward value-a computation thought to be essential for an animal to learn from its environment (8-10). In this way, LHb activity, which is aversive (1, 11-13), can provide "teaching" signals to an animal: increased LHb activity (i.e., if actual reward value is less than expected) discourages repeating a behavior in the future (11,12,14), while decreased LHb activity is thought to reinforce a behavior.Human and nonhuman animal studies indicate that stressinduced changes in LHb activity may contribute to depression by suppressing reward-based behavior (1,(15)(16)(17)(18). While stress decreases reward sensitivity (19,20), is a major risk factor for depression (21, 22), forms the basis for most animal models of depression (23-25), and causes plasticity in the LHb (26-31), its effects on LHb reward and RPE signals are not known.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, these data provide a dichotomy of Fs responses in the LHb that may be relevant for motivated states as well as for pathological condition characterized by LHb dysfunction including addiction and depression (Nuno-Perez, Tchenio, Mameli, & Lecca, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Em humanos, a participação da LHb no processamento de estímulos aversivos foi relevada em elegantes estudos de imagem mostrando de maneira consistente que a LHb é seletivamente ativada por desfechos negativos (ULLSPERGER; VON CRAMON, 2003;SHEPARD;HOLCOMB;GOLD, 2006). Em consonância com um possível papel chave na codificação de eventos aversivos, estudos em animais (CALDECOTT-HAZARD; MAZZIOTTA; PHELPS, 1988;AMAT et al, 2001) e humanos (MORRIS et al, 1999;SHEPARD;HOLCOMB;GOLD, 2006) apontaram que a hiperatividade da LHb é um fator importante em distúrbios do tipo depressivo (YANG et al, 2018;NUNO-PEREZ et al, 2018). Além disso, embora não haja projeções diretas entre a LHb e o hipocampo, foi recentemente demonstrado que uma LHb intacta é crítica para a codificação e resgate da memória espacial (GOUTAGNY et al, 2013;MATHIS et al, 2015), bem como para regular as oscilações teta do hipocampo (AIZAWA et al, 2013).…”
Section: Funções Da Hbunclassified